The Effect of Leadership Competences on Job Satisfaction in Government Organization in North Sulawesi Province - Ventje A. Senduk (Journal of International Conference Proceedings (JICP), 2018)
This study aims to analyze the relationship of leadership competence and its impact to build job satisfaction in the organization with a quantitative approach. The research was conducted in government organizations in the districts of North Sulawesi, using Survey or correlational method. Sampling technique is nonprobability sampling type. Data collection techniques are observation, questionnaire / questionnaire, interview and documentation. Based on the discussion of the results of research analysis found leadership competencies affect employee job satisfaction. Results of simple linear regression calculations Y=34,26+0,57. R2= 22,09 % and 77,11% influenced by other variables. Which means between leadership competence and employee job satisfaction there is a positive influence. Keywords: Leadership Competence, Employee Job Satisfaction